Behavioral and Synaptic Plasticity Are Impaired upon Lack of the Synaptic Protein SAP47. - Saumweber, T.; Weyhersmüller, A.; Hallermann, S.; Diegelmann, S.; Michels, B.; Bucher, D.; Funk, N.; Reisch, D.; Krohne, G.; Wegener, S.; Buchner, E.; Gerber, B. (Journal of Neuroscience, 2011)
The synapse-associated protein of 47 kDa (SAP47) is a member of a phylogenetically conserved gene family of hitherto unknown function. In Drosophila, SAP47 is encoded by a single gene (Sap47) and is expressed throughout all synaptic regions of the wild-type larval brain; specifically, electron microscopy reveals anti-SAP47 immunogold labeling within 30 nm of presynaptic vesicles. To analyze SAP47 function, we used the viable and fertile deletion mutant Sap47(156), which suffers from a 1.7 kb deletion in the regulatory region and the first exon. SAP47 cannot be detected by either immunoblotting or immunohistochemistry in Sap47(156) mutants. These mutants exhibit normal sensory detection of odorants and tastants as well as normal motor performance and basic neurotransmission at the neuromuscular junction. However, short-term plasticity at this synapse is distorted. Interestingly, Sap47(156) mutant larvae also show a 50% reduction in odorant-tastant associative learning ability; a similar associative impairment is observed in a second deletion allele (Sap47(201)) and upon reduction of SAP47 levels using RNA interference. In turn, transgenically restoring SAP47 in Sap47(156) mutant larvae rescues the defect in associative function. This report thus is the first to suggest a function for SAP47. It specifically argues that SAP47 is required for proper behavioral and synaptic plasticity in flies-and prompts the question whether its homologs are required for proper behavioral and synaptic plasticity in other species as well.